Serum PIVKA-II as a Preoperative Predictor of Microvascular Invasion and Tumor Proliferation in HBV-Related Hepatocellular Carcinoma - Irfansyah Irfansyah; Wifanto S. Jeo; Nur Rahadiani (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Hepatocellular carcinoma (HCC) contributes significantly to cancer-related mortality worldwide, particularly in hepatitis B–endemic regions such as Indonesia. The need for reliable preoperative biomarkers remains a major gap, especially to predict microvascular invasion (MVI) and tumor proliferation. PIVKA-II was specifically selected over AFP because of its superior ability to reflect tumor-invasive biology through MET and JAK/STAT pathway activation. Objective: This study aimed to assess whether serum PIVKA-II levels can predict MVI and Ki-67 proliferation index. Methods: A retrospective study was conducted on 20 patients with HBV-related HCC who underwent liver resection at Cipto Mangunkusumo Hospital (2017–2025). Serum PIVKA-II was categorized as high (>40 mAU/mL) or low (≤40 mAU/mL). MVI was identified histologically; Ki-67 expression was categorized as high (>20%) or low (≤20%) using immunohistochemistry. Results: PIVKA-II levels showed a significant relationship with AFP (p = 0.033) and BCLC stage (p = 0.038). ROC analysis showed that PIVKA-II had fair discriminative ability (AUC = 0.703) in predicting vascular invasion, with a sensitivity of 87.5% and specificity of 75%. There was a significant relationship between high PIVKA-II levels and the occurrence of vascular invasion (p = 0.032; RR = 2.33). However, PIVKA-II did not show good predictive ability for tumor cell proliferation (Ki-67) (AUC = 0.484), and no significant relationship was found between them (p = 0.530). Conclusion: PIVKA-II is a useful preoperative biomarker for predicting microvascular invasion in HBV-related HCC. Its lack of association with Ki-67 indicates that additional markers are needed to assess tumor proliferative behavior. These findings support the integration of PIVKA-II into preoperative risk assessment.